The Disruptive Fluidity and Ubiquity: Creativity in the World of In-betweenness - Piliang, Yasraf A. (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2024)
Fluidity and ubiquity are two fundamental principles of our contemporary world, representing new ways of perceiving, thinking, experiencing, organising, and creating various aspects of our present world. These principles have radically transformed models of economic exchanges, industrial production, social relations, cultural representations, and aesthetic expressions. Fluidity serves as a philosophical antithesis to the modern rigid, stratified, and binary worldview, celebrating a fluid, non-stratified, and non-binary perspective driven by dynamic flow, flux, and connectivity. On the other hand, ubiquity defines our present world of objects, which are created through augmented and mixed reality, giving them the property of being present anywhere and everywhere. Both fluidity and ubiquity serve as contemporary models for generating disruptive ideas, forms, styles, products, organisations, and systems. Fluidity represents the fluid-creative organisation of physical, social, cultural, and aesthetic elements, independent of binary structures, while ubiquity represents the transformation of objects from the virtual to the trans-material.